First observations of the rare decays B+ → K+π+π− [mu] + [mu] − and B+→ [phi] K+ [mu] + [mu] − - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (Journal of high energy physics, 2014)
First observations of the rare decays B+ → K+π+π−μ+μ−and B+→ ϕK+μ+μ− are presented using data corresponding to an integrated luminosity of 3.0 fb−1, collected by the LHCb experiment at centre-of-mass energies of 7 and 8 TeV. The branching fractions of the decays are
Im Titel sind "+" und "-" hochgestellt
Im Titel sind "mu" und "phi" als griechische Buchstaben dargestellt
Gesehen am 10.07.2020